Investigation of Dielectric Decrement and Correlation Effects on Electric Double-Layer Capacitance by Self-Consistent Field Model (Communications in Computational Physics, 2018)
The differential capacitance of electric double-layer capacitors is studiedby developing a generalized model of the self-consistent Gaussian field theory. Thismodel includes many-body effects of particles near the interface such as ionic sizes, theorder of water alignment and electrostatic correlations, and thus can present more accuratepredictions of the electric double-layer structure and hence the capacitance thantraditional continuum theories. Analytical simplification of the model and efficientnumerical method are introduced, in particular, the approximation of the self-Green'sfunction which describes the self energy of a mobile ion. We show that, when the appliedvoltage on interfaces is small the dielectric effect of the electrode materials playsan important role. For large voltage, this effect is screened, but the dielectric saturationdue to the alignment of the nearby water is shown to be essential. For 2:1 electrolytes,abnormal enhancement on the capacitance due to the dielectric electrode is observed,which is due to the interplay of the image charge effect and Born solvation energy inthe self energy of ions.